New species of oak gallwasps from Taiwan (Hymenoptera: Cynipidae: Cynipini) - Tang, Chang-Ti; Melika, George; Yang, Man-Miao; Nicholls, James A.; Stone, Graham N. (Zootaxa, 2011)
Three new species of oak gallwasps from Taiwan are described: Andricus songshui and Andricus pseudocurvator, both known to induce integral leaf galls on Quercus serrata, and Plagiotrochus glaucus which induces stem swelling-like galls on Quercus glauca. Galls and adults of new species are described; data on the diagnosis, distribution and biology of the new species and a key to the Taiwanese Andricus species are also given.